China's opening-up the impact on monetary policy choice - Zhiyong, Fan (Enrich series on China's economic issues, 2011)
This book looks at the characteristics of Chinas monetary policy since 1978, when China opened its door to private enterprises and the world. It provides a comprehensive study backed by theoretical and empirical researches in the following three aspects: The impact on the monetary transmission mechanism by the private sector; The identification of cost-push inflation and related monetary policy choices; Challenges and responses to Chinas monetary policy under the Open-Door policy.